KUALITAS PELAYANAN LIGHT RAIL TRANSIT (LRT) SUMATERA SELATAN DI KOTA PALEMBANG - Vika Vinertia; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Public transportation services serve as a key means of mobility for urban communities, making service quality an essential aspect of their management. The Light Rail Transit (LRT) South Sumatra, as one of the mass transportation modes, still faces several service-related challenges. This study aims to analyze service quality and identify the factors contributing to it. The research employs a qualitative descriptive method with data collected through interviews, observations, and documentation, using the five-dimensional service quality theory by Zeithaml, Parasuraman, and Berry (1990) in Hardiyansyah (2018:63), as well as the service quality factor theory by Albert and Zemke in Dwianto (2006:140). The findings indicate that overall service quality is good, although certain dimensions show deficiencies. In terms of tangibility, facilities such as lifts and escalators are not consistently operational. Regarding reliability, operational delays and suboptimal information delivery are still observed. For responsiveness, staff response is not always prompt, especially during peak periods. Meanwhile, the assurance and empathy dimensions show positive results through service security, fare certainty, and the courteous and professional attitude of staff. Supporting factors include the implemented strategies and the role of passengers in service use. However, system inefficiencies and limitations in human resources remain obstacles to optimal service delivery. Recommendations include improving facility maintenance, enhancing operational communication systems, and adjusting staff allocation to ensure more effective service performance.